King Rother - Lichtenstein, Robert (UNC Studies in the Germanic Languages and Literatures, 1962)
Originally published in 1962, Robert Lichtenstein's translation of "King Rother" made the medieval epic available to English-speaking audiences for the first time. His translation in rhymed couplets seeks to convey the humorous spirit of the original and an introduction places the poem in its historical context.